An evaluation of the University of Rizal System Morong's (URSM) University Library through users' assessment - Ramos, Eugene G.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
The study aims to determine the effectiveness level of the University of Rizal System Morong's current library policies and procedures (regarding service hours, loans, fines and other services) through a users' assessment which involves undergraduate students enrolled during the second semester, AY 2006-2007.
The study utilized the descriptive research method. A survey questionnaire was used as the principal instrument for data gathering which aims to obtain the following information: Respondent's profile; Library services and information needs; library policies and procedures; User's rating of the library. Using Slovin's formula, a total of 372 respondents were determined from the total population 5,305 students. The respondents were chosen using quota and purposive sampling and questionnaires were given to students from all year levels (including enrollees of supplemental units) from different courses in the university.
Results of the study show that majority of respondents visit the library 2 - 3 times a week, the majority of them saying they have access to other sources of information. Most students prefer to obtain their information through the Internet. The majority of the respondents are aware of the service policies and procedures of the URSM library. The respondents also agree with the current policies and procedures implemented in the library. The staff is given positive responses by the respondents, saying that they are approachable and are willing to help even if the users do not ask them first. The library staff is also efficient in providing the respondents their information needs in the shortest possible time, less than 5 minutes. The respondents also gave the library positive responses by saying that the library is both fair and consistent in the implementation of their service policies and procedures. The majority of the population is satisfied with the currently implemented policies and procedures.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of Rizal System Morong (URSM).; Academic libraries -- Philippines -- Rizal